Mapping the extent of heterogeneity of human CCR5+ CD4+ T cells in peripheral blood and lymph nodes. (1st May 2020) - Zaunders, John; Munier, C. Mee Ling; McGuire, Helen M.; Law, Hannah; Howe, Annett; Xu, Yin; de St Groth, Barbara Fazekas; Schofield, Peter; Christ, Daniel; Milner, Brad; Obeid, Solange; Dyer, Wayne B.; et al.
Abstract : Background: CD4 + T cells that express the chemokine receptor, CCR5, are the most important target of HIV-1 infection, but their functions, phenotypes and anatomical locations are poorly understood. We aimed to use multiparameter flow cytometry to better define the full breadth of these cells. Methods: High-parameter fluorescence flow and mass cytometry were optimized to analyse subsets of CCR5 + memory CD4 + T cells, including CD25 high CD127 dim Tregs, CXCR3 + CCR6− Th1-like, CCR6 + CD161 + CXCR3− Th17-like, integrins α4 + ß7 + gut-homing, CCR4 + skin-homing, CD62L + lymph node-homing, CD38 + HLA-DR + activated cells, and CD27−CD28− cytotoxic T lymphocytes, in a total of 22 samples of peripheral blood, ultrasound-guided fine needle biopsies of lymph nodes and excised tonsils. CCR5 + antigen-specific CD4 + T cells were studied using the OX40 flow-based assay. Results: 10–20% of CCR5 + memory CD4 + T cells were Tregs, 10–30% were gut-homing, 10–30% were skin-homing, 20–40% were lymph node-homing, 20–50% were Th1-like and 20–40% were Th17-like cells. Up to 30% were cytotoxic T lymphocytes in CMV-seropositive donors, including cells that were either CCR5 high Granzyme K + or CCR5 dim Granzyme B + . When all possible phenotypes were exhaustively analysed, more than 150 different functional and trafficking subsets of CCR5 + CD4 + T cells were seen. Moreover, a small population of resident CD69 + Granzyme K + CCR5 + CD4 + T cells was found in lymphoid tissues. CMV− and Mycobacterium tuberculosis -specific CD4 + T cells were predominantly CCR5 + . Conclusion: These results reveal for the first time the prodigious heterogeneity of function and trafficking of CCR5 + CD4 + T cells in blood and in lymphoid tissue, with significant implications for rational approaches to prophylaxis for HIV-1 infection and for purging of the HIV-1 reservoir in those participants already infected. Abstract : Supplemental Digital Content is available in the text